Factors affecting surgical margin recurrence after hepatectomy for colorectal liver metastases - Akyuz, Muhammet (Gland Surg, 2016)
BACKGROUND: Hepatic recurrence after resection of colorectal liver metastasis (CLM) occurs in 50% of patients during follow-up, with 2.8% to 13.9% presenting with surgical margin recurrence (SMR). The aim of this study is to analyze factors that related to SMR in patients with CLM undergoing hepatectomy. METHODS: Demographics, clinical and survival data of patients who underwent hepatectomy were identified from a prospectively maintained, institutional review board (IRB)-approved database between 2000 and 2012. Statistical analysis was performed using univariate Kaplan Meier and Cox proportional hazard model. RESULTS: There were 85 female and 121 male patients who underwent liver resection for CLM. An R0 resection was performed in 157 (76%) patients and R1 resection in 49. SMR was detected in 32 patients (15.5%) followed up for a median of 29 months (range, 3–121 months). A half of these patients had undergone R1 (n=16) and another half R0 resection (n=16). Tumor size, preoperative carcinoembryonic antigen (CEA) level and margin status were associated with SMR on univariate analysis. On multivariate analysis, a positive surgical margin was the only independent predictor of SMR. The receipt of adjuvant chemotherapy did not affect margin recurrence. SMR was an independent risk factor associated with worse disease-free (DFS) and overall survival (OS). CONCLUSIONS: This study shows that SMR, which can be detected in up to 15.5% of patients after liver resection for CLM, adversely affects DFS and OS. The fact that a positive surgical margin was the only predictive factor for SMR in these patients underscores the importance of achieving negative margins during hepatectomy.